Confirmatory Factor Analysis and Standardization of the Hospital Anxiety and Depression Scale (HADS) - Faro, André (2015)
The main objectives of this study were to perform a confirmatory factor analysis of the Hospital Anxiety andDepression Scale (HADS) and to conduct ROC curves for standardization of cut-off points, in a nonclinical sample. The resultsshowed evidences of the structural validity of HADS and changes were proposed to the diagnostic parameters of anxiety (â‰¥7points) and depression (â‰¥6 points). Finally, we highlight that caution is needed for the interpretation of the scores and diagnosticdecision, especially for the depression measure.